Role of Single Nucleotide Polymorphism of СУР17А Gene in the Development of Stroke - S. Yu. Nikulina; V. A. Shulman; A. A. Chernova; D. A. Nikulin; A. A. Semenchukov; O. V. Marilovceva; S. S. Tret'jakova; I. I. Lebedeva; V. N. Maksimov (Столичная издательская компания, 2018)
Background. The search for genetic predictors of stroke development is actively studied in all developed countries due to the need to address the primary prevention of socially significant diseases. Gene CYP17A1 is one of the many genes that can participate in the formation of predisposition to the development of stroke.Aim. To examine association of the single nucleotide polymorphisms rs1004467 CYP17A1 gene with the development of stroke.Material and methods. The study included 184 patients with stroke (active group; 113 men and 71 women; mean age 55.06±9.40 years), 131 of them with ischemic stroke and 41 with hemorrhagic stroke. The comparison group included 251 people with hypertension without stroke (160 men and 91 women; mean age 59.21±6.62 years) and control group - 157 persons without cardiovascular diseases (106 men and 51 women; mean age 54.94±6.64 years). Study participants underwent clinical (collection of complaints, anamnesis, physical examination), laboratory (blood chemistry, lipid profile) and instrumental (computer tomography of the brain, ultrasound duplex scanning of extraand intracranial blood vessels, electrocardiography, echocardioscopy) examination to verify the diagnosis, molecular genetic study of gene polymorphism СУР17А.Results. The study established the association of homozygous genotype AA rs1004467 CYP17A1 gene with the risk of stroke, which is confirmed bya statistically significant increase in the number of carriers of homozygous genotype AA in the common allele A rs1004467 CYP17A1 gene in patients of the main group (73.4±3.3%) compared to the control group (61.8±3.9%; p=0.03). Statistically significant increase in the number of carriers of genotype AA rs1004467 of CYP17A1 gene in patients with hemorrhagic stroke (70.7±7.1%) compared with the control (61.8±3.9%; p=0.01) was revealed. There are no statistically significant associations between the rs1004467 genotypes of CYP17A1 gene and the risk factors of stroke (hypercholesterinemia, burdened hereditary, hypertension, increased intima-media thickness of brachiocephalic arteries).Conclusions. The ability to consider the genetic determinants of brain stroke allows to identify proactively the risk factors of this complex cascade process. Studies of gene polymorphism as a factor of genetic predisposition to various human diseases allow to determine the individual possibilities of optimal therapy for each patient, considering the identified risk factors.